Robotic approach to the liver: Open surgery in a closed abdomen or laparoscopic surgery with technical constraints?. (June 2020) - Troisi, Roberto Ivan; Pegoraro, Francesca; Giglio, Mariano Cesare; Rompianesi, Gianluca; Berardi, Giammauro; Tomassini, Federico; De Simone, Giuseppe; Aprea, Giovanni; Montalti, Roberto; De Palma, Giovanni Domenico
Abstract: The application of the minimally invasive approach has shown to be safe and effective for liver surgery and is in constant growth. The indications for laparoscopic surgery are steadily increasing across the field. In the early 2000s, robotic surgery led to some additional improvements, such as tremor filtration, instrument stability, 3D view and more comfort for the surgeon. These techniques bring in some advantages compared to the traditional OLR: less blood loss, shorter admissions, fewer adhesions, and a faster postoperative recovery and better outcomes in case of further hepatectomy for tumor recurrence has been shown. Concerning which is the best minimally invasive approach between laparoscopic and robotic surgery, the evidence is still conflicting. The latter shows good potential, since the endo-wristed instruments work similarly to the surgeon's hands, even with an intact abdominal wall. However, the technique is still under development, burdened by important costs, and limited by the lack of some instruments available for the laparoscopic approach. The paucity of universally accepted and proven data, especially concerning long-term outcomes, hampers drawing univocal acceptance at present. Furthermore, the number of variables related both to the patient and the disease further complicates the decision leading to a treatment tailored to each patient with strict selection. This review aims to explore the main differences between laparoscopic and robotic surgery, focusing on indications, operative technique and current debated clinical issues in recent literature.